PENDAYAGUNAAN TEKNOLOGI INFORMASI DALAM DAKWAH UNTUK ANAK-ANAK TANTANGAN DAN PELUANG DI ERA DIGITAL - Lasmini Lasmini; Faturohman Husain (Sekolah Tinggi Pariwisata Mataram, 2023)
This article aims to find challenges and opportunities in preaching to children using information technology. This study uses a qualitative approach with the method of literature study and secondary data analysis. The results of the study show that the use of information technology in da'wah to children offers great opportunities to reach a wider audience, arouse children's interest in studying religion, facilitate accessibility to various sources of religious knowledge, and da'wah content conveyed through information technology can attract the attention of children according to the areas of interest. However, the challenge side also needs to be considered. Content that is inconsistent with religious values, such as dangerous or immoral content, can be easily accessed by children through information technology. It is important for parents, teachers and the community to always guide their children in using information technology. In this context, this study recommends that preachers and religious education actors must be more proactive in developing and managing appropriate and quality da'wah content in various information technology platforms. In addition, collaboration between preachers, parents, teachers and the government needs to be improved to create a digital environment that is safe and supports children in obtaining a good religious education